The complete chloroplast genome sequence of Eriobotrya fragrans. Issue 2 (3rd July 2019) - Dong, Zhanghong; Qu, Shaohong; Liu, Cheng; Ye, Peng; Xin, Peiyao
Abstract: Eriobotrya fragrans Champion ex Bentham is a potential medicinal plant of the genus Eriobotrya Lindl in the family Rosaceae. To better determine its phylogenetic location with respect to the other Rosaceae species, the complete chloroplast genome of E. fragrans was sequenced. The whole E. fragrans chloroplast genome is 159, 286 bp in length, consisting of a pair of inverted repeat (IR) regions of 26, 343 bp, one large single-copy (LSC) region of 87, 301 bp, and one small single-copy (SSC) region of 19, 299 bp. The overall GC content of the whole chloroplast genome is 36.7%. Further, phylogenetic analysis using maximum likelihood with TVM + F+R2 model strongly supports the relationship: sisterhood of E. fragrans and E. japonica, followed by three species of Pyrus L.